Perceptual Aspects of Postural Control: Does Pure Proprioceptive Training Exist?. Issue 3 (June 2018) - Nagy, Edit; Posa, Gabriella; Finta, Regina; Szilagyi, Levente; Sziver, Edit
As proprioceptive training is popular for injury prevention and rehabilitation, we evaluated its effect on balance parameters and assessed the frequency spectra of postural sway linked with the various sensory channels. We recorded the Center of Mass displacement of 30 healthy student research participants (mean age = 21.63; SD  = 1.29 years) with a single force plate under eyes open (EO) and eyes closed (EC) positions while standing on either a firm or foam surface, both before and after an 8-week balance training intervention on a foam surface with EC. We subjected the data to frequency power spectral analysis to find any differences between the frequency bands, linked with various sensory data. On the foam surface in the EC condition, the sway path decreased significantly after proprioceptive training, but, on the firm surface in the EC condition, there was no change. On the foam surface in the EC condition, there was also a significant decrease in frequency power postproprioceptive training in the medium-to-low frequency band. While our data indicate better posttraining balance skills, improvements were task specific to the trained condition, with no transfer of the acquired skill, even to a similar, easier condition. As training improved the middle-low frequency band, linked with vestibular signals, this intervention is better described as balance than "proprioceptive" training.